2021
DOI: 10.1093/mnras/stab2352
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on AGN activity via extinction-free mid-infrared census

Abstract: How does the environment affect active galactic nucleus (AGN) activity? We investigated this question in an extinction-free way, by selecting 1120 infrared galaxies in the AKARI North Ecliptic Pole Wide field at redshift z ≤ 1.2. A unique feature of the AKARI satellite is its continuous 9-band infrared (IR) filter coverage, providing us with an unprecedentedly large sample of IR spectral energy distributions (SEDs) of galaxies. By taking advantage of this, for the first time, we explored the AGN activity deriv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 125 publications
0
4
0
Order By: Relevance
“…Due to edge effects, previous studies (e.g., Miller et al 2003;Cooper et al 2005) removed these edge sources in their analyses. Santos et al (2021) proposed an edge correction method to estimate the correct local galaxy density by scaling the measured counts within a given radius by the amount of aperture area covered by the survey. We use the same edge correction method revised for aperture counts to measure the environment of our edge sources.…”
Section: Aperture Counts Edge Correction and Magnitude Cutmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to edge effects, previous studies (e.g., Miller et al 2003;Cooper et al 2005) removed these edge sources in their analyses. Santos et al (2021) proposed an edge correction method to estimate the correct local galaxy density by scaling the measured counts within a given radius by the amount of aperture area covered by the survey. We use the same edge correction method revised for aperture counts to measure the environment of our edge sources.…”
Section: Aperture Counts Edge Correction and Magnitude Cutmentioning
confidence: 99%
“…Our edge correction method is done under the assumption that galaxy densities are the same in and outside of the edge within the aperture. This also entails that increasing the aperture size will also increase the uncertainty or noise added to the edge-corrected density (Santos et al 2021). This correction would overestimate the density if the area outside of the edge is a lower density region (e.g.…”
Section: Aperture Counts Edge Correction and Magnitude Cutmentioning
confidence: 99%
See 1 more Smart Citation
“…At higher redshifts (1.4 z 2.5), Bornancini & García Lambas (2020) studied obscured and unobscured AGNs and QSOs, reporting the correlation of different AGN types with the environment. Santos et al (2021) using AKARI North Ecliptic Pole Wide field reported that, at redshift (0.7 z 1.2), AGN activity increases with an increase in environmental density. Ellison et al (2011) used SDSS to show that the fraction of AGN galaxy with a close companion is higher compared to a control sample and concluded that interaction plays a role in triggering AGN activity.…”
Section: Introductionmentioning
confidence: 99%